Postnatal Maturation of Glutamatergic Inputs onto Rat Jaw-closing and Jaw-opening Motoneurons. (1st January 2022) - Nakamura, Shiro; Kajiwara, Risa; Noguchi, Tsuyoshi; Nakayama, Kiyomi; Mochizuki, Ayako; Dantsuji, Masanori; Sarkar, Avijite Kumer; Inoue, Tomio
Highlights: A diversity of developmental changes in the trigeminal motoneurons was observed. Jaw-closing motoneurons showed decreased decay time of non-NMDA mEPSCs with age. The NMDA EPSCs are predominant in early postnatal jaw-closing motoneurons. Jaw-opening motoneurons did not undergo age-related changes in the EPSCs. These distinct features may subserve the development of feeding behavior. Abstract: Motoneurons that innervate the jaw-closing and jaw-opening muscles play a critical role in oro-facial behaviors, including mastication, suckling, and swallowing. These motoneurons can alter their physiological properties through the postnatal period during which feeding behavior shifts from suckling to mastication; however, the functional synaptic properties of developmental changes in these neurons remain unknown. Thus, we explored the postnatal changes in glutamatergic synaptic transmission onto the motoneurons that innervate the jaw-closing and jaw-opening musculatures during early postnatal development in rats. We measured miniature excitatory postsynaptic currents (mEPSCs) mediated by non-NMDA receptors (non-NMDA mEPSCs) and NMDA receptors in the masseter and digastric motoneurons. The amplitude, frequency, and rise time of non-NMDA mEPSCs remained unchanged among postnatal day (P)2–5, P9–12, and P14–17 age groups in masseter motoneurons, whereas the decay time dramatically decreased with age. The properties of the NMDA mEPSCs were more predominant at P2–5 masseter motoneurons, followed by reduction as neurons matured. The decay time of NMDA mEPSCs of masseter motoneurons also shortened remarkably across development. Furthermore, the proportion of NMDA/non-NMDA EPSCs induced in response to the electrical stimulation of the supratrigeminal region was quite high in P2–5 masseter motoneurons, and then decreased toward P14–17. In contrast to masseter motoneurons, digastric motoneurons showed unchanged properties in non-NMDA and NMDA EPSCs throughout postnatal development. Our results suggest that the developmental patterns of non-NMDA and NMDA receptor-mediated inputs vary among jaw-closing and jaw-opening motoneurons, possibly related to distinct roles of respective motoneurons in postnatal development of feeding behavior.